HMGB1, the Next Predictor of Transcatheter Arterial Chemoembolization for Liver Metastasis of Colorectal Cancer? - Sun, Yuan-dong; Zhang, Hao; Chen, Ye-qiang; Wu, Chun-xue; Zhang, Jian-bo; Xu, Hui-rong; Liu, Jing-zhou; Han, Jian-jun (Frontiers in Oncology, 2020)
Highlight：The findings of this study suggest that patients with low expression of HMGB1 before TACE have a lower incidence of severe liver damage. Postoperative liver damage is proportional to the preoperative expression level of HMGB1. Respondents who reported lower levels of HMGB1 also reported significantly lower liver damage. The findings from these studies suggest that higher HMGB1 expression levels before TACE can influence liver damage and efficacy. Taken together, these results suggest that patients with severe HMGB1 changes after TACE had more severe liver damage and were less sensitive to TACE treatment, but ORR and PFS were relatively better. These results confirm the association among HMGB1, and liver damage and efficacy.HMGB1 is an important mediator of inflammation during ischemia-reperfusion.The serum expression of HMGB1 was increased significantly on the 1st day after treatment. A decreased significantly which was lower on the 30th day after TACE. Posttumor markers decreased significantly. Patients had a transient immune disorder after the treatment. The correlational analysis shown the low HMGB1 expression patients had lower risks of fever and liver injury with the higher expression, while the ORR is relatively worse. Patients with lower expression of HMGB1 had longer PFS, better treatment outcomes, and higher quality of life. With the high post-expression, the low expression had lower incidence of fever and liver injury too. There was no statistical difference in the one-year survival among the different patients. The quality of life of all patients was improved significantly. The over-expression of HMGB1 in LMCRC is an adverse prognostic feature and a positive predictor of response to TACE.